2018
DOI: 10.1021/acs.est.7b04226
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of Bisphenol S Showing Immunomodulation in Fish Macrophages

Abstract: Bisphenol S (BPS), a structural analogue of bisphenol A (BPA), has been increasingly used as a common replacement of BPA due to health concerns regarding the former. However, mounting evidence suggests that BPS has similar endocrine-disrupting effects as BPA, and likewise, its presence in the environment may pose considerable risks to ecosystems and human health. Using fish primary macrophages (fpMQs), we here evaluated the immunomodulatory effects of BPS and its mechanisms of action associated with estrogen r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…83 Qiu et al also found that BPS could cause severe oxidative stress at higher BPS exposure concentrations, subsequently destroying cell homeostasis and promoting apoptosis. 13 Based on our studies, we hypothesized that BPS may affect apoptosis by oxidative stress and thus affect the lifespan of C. elegans.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…83 Qiu et al also found that BPS could cause severe oxidative stress at higher BPS exposure concentrations, subsequently destroying cell homeostasis and promoting apoptosis. 13 Based on our studies, we hypothesized that BPS may affect apoptosis by oxidative stress and thus affect the lifespan of C. elegans.…”
Section: Discussionmentioning
confidence: 96%
“…[8][9][10] Bisphenol S is a structural analog of bisphenol A which is widely used as a substitute in a variety of products such as baby bottles, thermal receipt paper, food packaging materials and personal care products. 2,[11][12][13] In Europe, the annual production of BPS is between 1000 and 10 000 t, and steadily increases. 14 In 2013, the detection concentration of BPS in Taihu Lake was 2 ng L −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, BPA, BPS, and BPAF differentially recruit co-regulators to the bisphenol-ER-a complex; this could be one possible reason for differential biological actions induced by these agents. Qiu et al (2018) showed that INFc,TNFa, mRNA expression in association with increased expression of both ER-a and -b in fish primary macrophages (isolated from head kidney of Cyprinus carpio). BPA-induced ER-a signaling can lead to increased activation of ERK/MAPK and PI3K/AKT pathways (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These evidences show that LPS‐induced macrophage activation can be inhibited by BPA. In contrast, expression of proinflammatory cytokines including IL‐1β, TNFα, and IL‐6 are induced by BPA in human macrophages, THP‐1 cells, and fish macrophages . Generation of NO and expression of iNOS is induced by BPA in fish macrophages .…”
Section: Discussionmentioning
confidence: 94%